Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) 9-25=(7-x)-(25+7)
(7-x)-(25+7)=9-25
(7-x)-(25+7)=-16
(7-x)-32=-16
7-x=-16+32
7-x=16
x=7-16
x=-9
2) (27-514) -(486-73)+x=7
(27-514) -(486-73)+x=7
-487-413+x=7
-1011+x=7
x=7-(-1011)
x=7+1011
x=1018
3) 25+5+37-25+6-29-x=37
25+5+37-25+6-29-x=37
67-25+6-29-x=37
42+6-29-x=37
48-29-x=37
19-x=37
x=19-37
x=-18
4) 14+(-12)+x =10-/-15/+ /-3/
14+(-12)+x =10-15+3
14+(-12)+x =-5+3
14+(-12)+x =-2
2+x=-2
x=-2-2
x=-4
\(\left(4\frac{5}{37}-3\frac{4}{5}+8\frac{15}{29}\right)-\left(3\frac{5}{37}-6\frac{14}{29}\right)\)
\(\left(4\frac{5}{37}-3\frac{4}{5}+8\frac{15}{29}\right)-\left(3\frac{5}{37}-6\frac{14}{29}\right)\)
a) \(x+\left(-7\right)=-20\)
\(\Rightarrow x=-20+7\)
\(\Rightarrow x=-13\)
Vậy \(x=-13\)
b) \(8-x=-12\)
\(\Rightarrow x=8-\left(-12\right)\)
\(\Rightarrow x=20\)
Vậy \(x=20\)
c) \(|x|-7=-6\)
\(\Rightarrow|x|=-6+7\)
\(\Rightarrow|x|=1\)
\(\Rightarrow\orbr{\begin{cases}x=1\\x=-1\end{cases}}\)
Vậy \(x\in\left\{1;-1\right\}\)
d) \(5^2.2^2-7.|x|=65\)
\(\Rightarrow\left(5.2\right)^2-7.|x|=65\)
\(\Rightarrow10^2-7.|x|=65\)
\(\Rightarrow100-7.|x|=65\)
\(\Rightarrow7.|x|=35\)
\(\Rightarrow|x|=5\)
\(\Rightarrow\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)
Vậy \(x\in\left\{5;-5\right\}\)
e) \(37-3.|x|=2^3-4\)
\(\Rightarrow37-3.|x|=8-4\)
\(\Rightarrow37-3.|x|=4\)
\(\Rightarrow3.|x|=33\)
\(\Rightarrow|x|=11\)
\(\Rightarrow\orbr{\begin{cases}x=11\\x=-11\end{cases}}\)
Vậy \(x\in\left\{11;-11\right\}\)
f) \(|x|+|-5|=|-37|\)
\(\Rightarrow|x|+5=37\)
\(\Rightarrow|x|=32\)
\(\Rightarrow\orbr{\begin{cases}x=32\\x=-32\end{cases}}\)
Vậy \(x\in\left\{32;-32\right\}\)
g)\(5.|x+9|=40\)
\(\Rightarrow|x+9|=8\)
\(\Rightarrow\orbr{\begin{cases}x+9=8\\x+9=-8\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=-1\\x=-17\end{cases}}\)
Vậy \(x\in\left\{-1;-17\right\}\)
h) \(-\frac{5}{6}+\frac{8}{3}+\frac{-29}{6}\le x\le\frac{-1}{2}+2+\frac{5}{2}\)
\(\Rightarrow\frac{-5}{6}+\frac{16}{6}+\frac{-29}{6}\le x\le\frac{-1}{2}+\frac{4}{2}+\frac{5}{2}\)
\(\Rightarrow-3\le x\le4\)
Vậy \(-3\le x\le4\)
b) 17x – ( -16x – 37) = 2x + 43
-> 33x +37 =2x +43
->31x=6
-> x= 6/31
c) -2x –3. (x – 17) = 34 – 2(-x + 25)
->-5x + 51= 2x-16
->7x= 67
x= 67/7
d) (-x - 6) (x + 9) = 0
Ta có (-x-6)= 0 hoặc (x+9)=0
-> x=-6 hoặc x=-9
1) $(-81)\cdot27-3^4\cdot(-77)$
$=(-81)\cdot27-81\cdot(-77)$
$=-81\cdot[27+(-77)]$
$=-81\cdot(27-77)$
$=-81\cdot(-50)$
$=81\cdot50$
$=4050$
2) $(-16)\cdot32-(-4)^2\cdot18$
$=(-16)\cdot32-16\cdot18$
$=-16\cdot(32+18)$
$=-16\cdot50$
$=-800$
3) $(-2)^4\cdot289-16\cdot189$
$=16\cdot289+16\cdot(-189)$
$=16\cdot[289+(-189)]$
$=16\cdot(289-189)$
$=16\cdot100$
$=1600$
4) $41\cdot(-18)+41\cdot(-81)-41$
$=1\cdot(-18)+41\cdot(-81)+41\cdot(-1)$
$=41\cdot[(-18)+(-81)+(-1)]$
$=41\cdot(-18-81-1)$
$=41\cdot(-99-1)$
$=41\cdot(-100)$
$=-4100$
5) $17\cdot(-37)-23\cdot37-46\cdot(-37)$
$=17\cdot(-37)+23\cdot(-37)-46\cdot(-37)$
$=-37\cdot(17+23-46)$
$=-37\cdot(40-46)$
$=-37\cdot(-6)$
$=37\cdot6$
$=222$
6) $-48+48\cdot(-78)+48\cdot(-21)$
$=48\cdot(-1)+48\cdot(-78)+48\cdot(-21)$
$=48\cdot[(-1)+(-78)+(-21)]$
$=48\cdot(-1-78-21)$
$=48\cdot(-79-21)$
$=48\cdot(-100)$
$=-4800$
7) $29\cdot(-13)+27\cdot(-29)+(-14)\cdot(-29)$
$=-29\cdot13+27\cdot(-29)+(-14)\cdot(-29)$
$=-29\cdot[13+27+(-14)]$
$=-29\cdot(40-14)$
$=-29\cdot26$
$=-754$
$\text{#}Toru$
37-2*(x+6)=29
2*(X+6) = 8
X + 6 = 4
X = -2